Book-Carriers – An Ideal of Lithuanianness - Juozaitis, Arvydas (Sociologija. Mintis ir veiksmas, 2001)
Article deals with the problem of social and historic being as the mainstream of the national rebirth. The strife for a real-being was the utter problem for the Lithuania national revival in XIX c. The activities of book-carriers has been the most acceptable form of the liberation movement. The symbolic fig ure of book-carrier is underlined in this survey as the central historical subject not only for 19 c. The vitality of the symbol is obvious for the all modern life. It links the 20th c. of Lithuania with the history of the country and its mentality at the end of 20 c.